Alcohol-related mortality in 15-24-year-olds in Denmark (2010-2019): a nationwide exploratory study of circumstances and socioeconomic predictorsResearch in context - Caroline Holt Udesen; Signe Skovgaard Hviid; Ulrik Becker; Janne S. Tolstrup (Elsevier, 2023)
Summary: Background: Adolescents and young adults aged 15-24 years are disproportionately affected by unnatural deaths, including accidents, suicide and interpersonal violence for which alcohol is a leading risk factor. We aimed to explore the extent of and circumstances surrounding alcohol-related deaths in young people aged 15-24 years and whether socioeconomic background and ethnicity differ in those who died due to alcohol-related causes as compared to the background population. Methods: All deaths of 15-24-year-olds occurring in Denmark from 2010 to 2019 were investigated. We manually reviewed death certificates containing information on circumstances, results from autopsies and blood tests, and statements from witnesses. Relevant information published in the media (most often newspaper articles) was included. Our main outcome measures were alcohol-related death and manner of death (accidents (transport accidents, drownings, falls, poisonings), suicide and violence). Further, we designed a population-based case-control study including 10 age- and sex-matched controls per case to test whether there was a socioeconomic gradient in alcohol-related deaths. We used parents' educational level and employment status to define socioeconomic position. Immigration status was used to assess ethnicity. Findings: Over the 10-year period, 1783 deaths occurred among 15-24-year-olds. Of those, 1067 (60%) were due to unnatural causes, corresponding to a mortality rate of 14.8 (95% confidence interval: 13.9-15.7) per 100,000. Twelve percent of unnatural deaths (n = 125) were alcohol related, corresponding to a rate of 1.7 (1.4-2.0) per 100,000, and were higher in males (2.9 [2.3-3.4]) than in females (0.6 [0.3-0.8]); thus, males accounted for 105 (84%) of alcohol-related deaths. The majority of alcohol-related deaths occurred on Fridays, Saturdays and Sundays (n = 77, 62%). Accidents accounted for 82% (n = 102) of alcohol-related deaths, followed by suicide (n = 19, 15%) and interpersonal violence (n = 4, 3%). Of all fatal accidents, 102 of 636 (16%) were alcohol related. Of all deaths caused by drownings and falls, 14 of 26 (54%) and 10 of 25 (40%), respectively, were alcohol related. Alcohol-related drownings most often occurred while the deceased was alone, whereas alcohol-related falls most often occurred in relation to parties, involving falls from a window or balcony. Those who died from alcohol-related causes more often had parents with a short education or who were unemployed, as compared to the general population. For example, odds ratios were 3.9 (2.2-7.0) and 1.8 (1.2-2.9) for having parents with short and medium as compared to long educations. The odds ratio for being of Danish origin was 4.0 (1.7-9.5) compared to being first- or second-generation immigrants. Interpretation: In 15-24-year-olds, alcohol-related deaths accounted for a substantial proportion of all unnatural deaths. There was substantial socioeconomic inequality in alcohol-related deaths, as has repeatedly been shown for chronic alcohol-related mortality in older adults. Funding: Trygfonden.